Students’ Perceptions Regarding the University Education Outcomes and Labor Market Requirements: Empirical Study - Rebaz Nooradeen Aziz; Hussein Ahmad Mustafa (Eurasian Journal of Management & Social Sciences)
The primary purpose of this research is to examine students’ perceptions regarding the university education outcomes and labour market requirements, empirical study in the college of administration and economics, Salahuddin University –Erbil. To collect data, the researchers used a self-designed questionnaire. The samples comprised (335) four-stage students for the academic year 2021-2022, randomly selected from six departments: administration of tourism organizations, business administration, economics, accounting, statistics and information, finance, and banking reply to the survey questions. The empirical data was examined using structural equation modelling (SEM). Findings based on students’ perceptions showed that professional knowledge is positively related to labour market requirements. At the same time, the courses and learning ability are not correlated with labour market requirements. In addition, students’ language skills are not connected with the labour market requirements which means that students who participated in the survey obtained basic knowledge regarding the labour market, but they lack the training to improve their skills. The research contributes to the literature, and also provides unique information that benefits the universities in boosting the quality of education services to align with the requirements labour market in the Kurdistan Region.